The Challenges of Quality Assurance Agencies (Revista Electrónica Calidad en la Educación Superior, 2024)
This article explores the challenges faced by quality assurance agencies (QAA) in Ibero-American higher education following the COVID-19 pandemic. It analyzes how these agencies have responded to significant changes in teaching modalities, the integration of new technologies, and evolving student demands. The article highlights the need for adaptability in the face of new educational models and alternative credential evaluations, proposing strategies to strengthen QAA through flexible approaches, international cooperation, and the use of technology. It emphasizes their essential role in ensuring educational quality and relevance in a dynamic context.
Keywords: Quality Assurance; higher education; post-pandemic; Ibero-America; accreditation agencies